The pyroptosis-related gene signature predicts prognosis and reveals characterization of the tumor immune microenvironment in acute myeloid leukemia - Zhou, Tao; Qian, Kai; Li, Yun-Yun; Cai, Wen-Ke; Yin, Sun-Jun; Wang, Ping; He, Gong-Hao (Frontiers in Pharmacology, 2022)
Background: Pyroptosis is a novel inflammatory form of programmed cell death and a prospective target for cancer therapy. Nevertheless, little is known about the association between pyroptosis-related genes (PRGs) and Acute myeloid leukemia (AML) prognosis. Herein, we systematically investigated the specific functions and clinical prognostic value of multiple PRGs in AML. Methods: Univariate and LASSO Cox regression analysis based on TCGA and GTEx database was used to generate PRG signature, whose predictive efficacy of survival was evaluated using survival analysis, ROC, univariate and multivariate Cox analysis as well as subgroup analysis. The BeatAML cohort was used for data validation. Association between risk score and immune cell infiltration, HLA, immune checkpoints, cancer stem cell (CSC), tumor mutation burden (TMB), and therapeutic drug sensitivity were also analyzed. Results: A 6-PRGs signature including CASP3, ELANE, GSDMA, NOD1, PYCARD, and VDR was generated. The high-risk score represented a poorer prognosis and the PRG risk score was also validated as an independent predictor of prognosis. A nomogram including cytogenetic risk, age, and risk score was constructed for accurate prediction of 1-, 3- and 5-year survival probabilities. Meanwhile, this risk score was significantly associated with the tumor immune microenvironment (TIME). A high-risk score is characterized by high immune cell infiltration, HLA and immune checkpoints, as well as low CSC and TMB. Additionally, patients with low-risk score presented significantly lower IC50 values for ATRA, cytarabine, midostaurin, doxorubicin, and etoposide. Conclusion: Our findings might contribute to further understanding of PRGs in the prognosis and development of AML and provide novel and reliable biomarkers for its precise prevention and treatment. Keywords: pyroptosis, acute myeloid leukemia, prognosis, immune microenvironment, TCGA